Phylogeographic analysis of the full genome of Sweepovirus to trace virus dispersal and introduction to Korea - Kim, Jaedeok (PLoS One, 2018)
Sweet potato is a vegetatively propagated crop that is produced for both growth in Korean fields and for export out of the country. The viruses that are present in introduced sweet potatoes can spread both domestically and to foreign countries. Determining the time and path of virus movement could help curtail its spread and prevent future dispersal of related viruses. Determining the consequences of past virus and sweet potato dispersal could provide insight into the ecological and economic risks associated with other sweet potato-infecting viral invasions. We therefore applied Bayesian phylogeographic inferences and recombination analyses of the available Sweepovirus sequences (including 25 Korean Sweepovirus genomes) and reconstructed a plausible history of Sweepovirus diversification and movement across the globe. The Mediterranean basin and Central America were found to be the launchpad of global Sweepovirus dispersal. Currently, China and Brazil are acting as convergence regions for Sweepoviruses. Recently reported Korean Sweepovirus isolates were introduced from China in a recent phase and the regions around China and Brazil continue to act as centers of Sweepovirus diversity and sites of ongoing Sweepovirus evolution. The evidence indicates that the region is an epidemiological hotspot, which suggests that novel Sweepovirus variants might be found.